PROGRAM OF FORMING CULTURE OF COMMUNICATION IN THE NETWORK OF THE INTERNET IN FUTURE FACULTY OF THE SOCIAL SPHERE - Шатило, Ю. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2019)
The article examines the conceptual theoretical approaches to the study of the problem of forming a culture of communication in the Internet on future specialists in the social sphere. The article reveals the importance of studying the problem of the culture of communication in the Internet of students of higher educational institutions. In the article a generalized analysis of the essence of the concepts "culture", "culture of communication", "Internet network", "culture of communication on the Internet" is carried out. The article determines that the culture of Internet communication can be defined as a component of the general professional culture of a specialist reflecting the level of knowledge gained within the global computer Internet environment, technologies and ethical norms of exchange of information, skills and abilities of interaction in computer networks and use them in practical activity according to their own value orientations and orientations. The article clarifies that the formation of the culture of communication of students in the Internet plays an important role in shaping the professional and communicative competence of future professionals in the social sphere. The author offers the main aspects of a practical program for creating a culture of communication on the Internet from future specialists in the social sphere. The author presents for familiarization the components of the culture of communication in the network, stages of the program, blocks, indicators, basic forms and methods of work